Global soil distribution, dietary access routes, bioconversion mechanisms and the human health significance of selenium: A review. (June 2021) - Ekumah, John-Nelson; Ma, Yongkun; Akpabli-Tsigbe, Nelson Dzidzorgbe Kwaku; Kwaw, Emmanuel; Ma, Shengmei; Hu, Jie
Abstract: Selenium (Se) is a required micronutrient with numerous health implications for all life forms. Organic Se species are considered nutritionally beneficial since they are highly bioavailable and innocuous. Nonetheless, access to organic Se in nature has been a challenge. This is due to the uneven global Se distribution with the resulting incidences of deficiency and toxicological disorders. Remedies for organic Se inaccessibility include the use of different approaches such as genetic engineering, Se fertilizer applications and the use of microorganisms. There are, however, several other unexplored opportunities to harness inorganic Se from Se endemic soil to bio-convert them to organic Se species and then into ready to eat functional foods and beverages for human health. Therefore, to better understand the concept of organic Se in human nutrition and health, this review highlights Se and selenoproteins and their antioxidative effects on human health. It further stresses the Se distribution in nature; dietary sources and the recommended daily allowance based on demographic factors; current plants and microbial bioconversion and food fortification approaches as well as available opportunities for Se research.